Electrochemical redox signaling of hemoglobin in human whole blood and its relevance to anemia and thalassemia diagnosis. Issue 7 (29th February 2016) - Amreen, Khairunnisa; Kumar, Annamalai Senthil
Abstract : Direct electron transfer behaviour of hemoglobin in human whole blood on mesoporous carbon modified electrode and its clinical relevance to hemoglobin analysis and thalassemia disease diagnosis was demonstrated. Abstract : A highly redox active human whole blood–carbon nanomaterial modified electrode has been developed, which showed a redox peak ( vs . Ag/AgCl) similar to that of hemoglobin ( vs . Ag/AgCl) in red blood cells. Clinical relevance of this for direct electrochemical analysis of blood hemoglobin content (anemia) and thalassemia disease diagnosis was demonstrated.